Maladaptive Perfectionism and Depression: Testing the Mediating Role of Self-Esteem and Internalized Shame in an Australian Domestic and Asian International University Sample - Dorevitch, Benjamin; Buck, Kimberly; Fuller-Tyszkiewicz, Matthew; Phillips, Lisa; Krug, Isabel (Frontiers in Psychology, 2020)
Objectives: To assess whether maladaptive perfectionism (parental and intrapersonal), mediated by self-esteem and internalised shame, lead to depressive symptoms, and to identify whether this model was invariant (i.e. structurally unchanged) across groups of Australian domestic and Asian international students. Method: A total of 624 (308 Australian domestic and 316 Asian international undergraduate university students) completed a questionnaire on the variables of interest. Results: Australian domestic and Asian international students did not significantly differ in reported levels of study variables apart from parental maladaptive perfectionism, on which Australian domestic students scored significantly higher. The proposed path-model differed across student groups, with findings indicating that intrapersonal maladaptive perfectionism impacted indirectly on depressive symptoms through internalised shame in both groups, however, indirectly through self-esteem in only the Asian international student group. Conclusions: Intrapersonal maladaptive perfectionism may be a culturally-independent process, capable of predisposing all university students to develop depressive symptoms, but that self-esteem may be a particularly relevant mediator of this relationship among Asian international students. Keywords: Depression, perfectionism, internalised shame, self-esteem, international students